PCSK9 Variants in Familial Hypercholesterolemia: A Comprehensive Synopsis - Guo, Qianyun; Feng, Xunxun; Zhou, Yujie (Frontiers in Genetics, 2020)
Autosomal dominant familial hypercholesterolemia (FH) affects approximately 1/250 individuals and potentially leads to elevated blood cholesterol and a significantly increased risk of atherosclerosis. Along with improvements in detection and the increased early diagnosis and treatment, the serious burden of FH on families and society has become increasingly apparent. Since FH is strongly associated with proprotein convertase subtilisin/kexin type 9 (PCSK9), increasing numbers of studies have focused on finding effective diagnostic and therapeutic methods based on PCSK9. At present, as PCSK9 is one of the main pathogenic FH genes, its contribution to FH deserves more explorative research.